1957
DOI: 10.1111/j.1365-2389.1957.tb01873.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Basaltic Soils of Northern Ireland

Abstract: Descriptions and analytical data are given relating to nine basaltic profiles representing soils which have been used in detailed studies on cation-exchange properties and mineralogical constitution of basaltic soils in Northern Ireland.Three main groups of soils are considered : those with impeded or poor drainage, those with free drainage, and those which have good drainage in the agricultural sense but which show slight signs of mottling in lower horizons. In all three groups of basaltic soils the clay cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1958
1958
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…of the silts increase down the profile, the contribution by this separate to the C.E.C. of the soils will be considerable, especially in the lower horizons (McAleese and McConaghy, 1957). Whilst feldspars (which are considered to have negligible C. E.C.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…of the silts increase down the profile, the contribution by this separate to the C.E.C. of the soils will be considerable, especially in the lower horizons (McAleese and McConaghy, 1957). Whilst feldspars (which are considered to have negligible C. E.C.…”
Section: Resultsmentioning
confidence: 98%
“…Silt separates as isolated by the ordinary International Method of mechanical analysis are shown to contribute considerably to the total C.E.C. of the soils (McAleese and McConaghy, 1957), and in some cases these contributions are greater than those for the corresponding clay se arates. which is regarded as t K e seat of the physico-chemical activity, e.g.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…per cent.-i.e. as high as or higher than those for corresponding clay separates (McAleese and McConaghy, 1957). Sand fractions were also found to have appreciable exchange capacities.…”
mentioning
confidence: 76%
“…Studies in the 1950s and 1960s indicated that the P fertility status of these soils could be difficult to determine. Some basaltic soils with very low extractable phoshorus (P) values were found to give good crop yields without P additions, whereas others did not (McConaghy 1955;McConaghy & Stewart 1963). Bailey et al (2000) noted that P recommendations (MAFF 1994) for basaltic soils, based on Olsen-P measurements, were completely unrelated to herbage P status, implying that the Olsen test had erroneously assessed the plant-available P contents.…”
Section: Introductionmentioning
confidence: 99%